β-Catenin Phosphorylated at Serine 45 Is Spatially Uncoupled from β-Catenin Phosphorylated in the GSK3 Domain: Implications for Signaling - Maher, Meghan T.; Mo, Rigen; Flozak, Annette S.; Peled, Ofra N.; Gottardi, Cara J. (PLOS ONE, 2010)
C. elegans and Drosophila generate distinct signaling and adhesive forms of β-catenin at the level of gene expression. Whether vertebrates, which rely on a single β-catenin gene, generate unique adhesive and signaling forms at the level of protein modification remains unresolved. We show that β-catenin unphosphorylated at serine 37 (S37) and threonine 41 (T41), commonly referred to as transcriptionally Active β-Catenin (ABC), is a minor nuclear-enriched monomeric form of β-catenin in SW480 cells, which express low levels of E-cadherin. Despite earlier indications, the superior signaling activity of ABC is not due to reduced cadherin binding, as ABC is readily incorporated into cadherin contacts in E-cadherin-restored cells. β-catenin phosphorylated at serine 45 (S45) or threonine 41 (T41) (T41/S45) or along the GSK3 regulatory cassette S33, S37 or T41 (S33/37/T41), however, is largely unable to associate with cadherins. β-catenin phosphorylated at T41/S45 and unphosphorylated at S37 and T41 is predominantly nuclear, while β-catenin phosphorylated at S33/37/T41 is mostly cytoplasmic, suggesting that β-catenin hypophosphorylated at S37 and T41 may be more active in transcription due to its enhanced nuclear accumulation. Evidence that phosphorylation at T41/S45 can be spatially separated from phosphorylations at S33/37/T41 suggests that these phosphorylations may not always be coupled, raising the possibility that phosphorylation at S45 serves a distinct nuclear function.